Mechanisms of Clostridioides difficile glucosyltransferase toxins and their roles in pathology: insights and emerging therapeutic strategies - Wen, Xin; Liu, Xue; Wan, Kai; Liu, Hong; Zhang, Cheng; Zhang, Xi; Wen, Qin (Frontiers in Cellular and Infection Microbiology, 2025)
Clostridioides difficile infection (CDI) is a significant cause of antibiotic-associated diarrhea and pseudomembranous colitis, manifesting as mild diarrhea, fulminant colitis, and even death. It is typically recognized as a healthcare-associated infection. Glucosyltransferase toxin A (TcdA) and toxin B (TcdB) are two major factors responsible for the pathogenicity of Clostridioides difficile (C. difficile). They bind to cell surface receptors and enter the cytoplasm via pH-dependent pore formation, causing cell death by inactivating GTPase. This review elucidates the pathogenic mechanisms of C. difficile glucosyltransferase toxins and discusses the interactions between the two toxins and host cells. It also summarizes current progresses in CDI therapies, providing a comprehensive understanding of the disease and laying the foundation for developing novel therapies and management strategies.